2018
DOI: 10.1080/17458080.2018.1511923
|View full text |Cite
|
Sign up to set email alerts
|

Tribological behavior of ZnO-Si3N4 nanoparticles-based lubricating grease

Abstract: Currently, nanoparticles have been widely used as lubricant additives, few researches have investigated their applications as additives for lubricating grease. In this paper, mixtures of ZnO and Si 3 N 4 nanoparticles were added into grease as additives. XRD and TEM were utilized to the investigate phase composition, microstructure and morphology of the nanomaterials. The composite grease was prepared by introducing ZnO and Si 3 N 4 nanoparticles into the grease matrix through ultrasonic dispersion. Then, trib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…44,51,57 For instance, He et al demonstrated that composite grease based on ZnO-Si 3 N 4 NPs has excellent potential for vibration reduction and temperature rise in high-speed bearings (55 000 rpm), coupled with excellent properties of lubrication and antifriction. 58 Another aspect of incorporating NPs as additives is their impact on grease's microstructure and rheological behaviour, but firstly, it is better to classify grease lubrication phases to comprehend the possible role of NPs. It is possible to classify the grease lubricating phases into two stages, based on the film thickness.…”
Section: Nps Tribological Role In Greases Form Evs Lubrication Perspe...mentioning
confidence: 99%
See 1 more Smart Citation
“…44,51,57 For instance, He et al demonstrated that composite grease based on ZnO-Si 3 N 4 NPs has excellent potential for vibration reduction and temperature rise in high-speed bearings (55 000 rpm), coupled with excellent properties of lubrication and antifriction. 58 Another aspect of incorporating NPs as additives is their impact on grease's microstructure and rheological behaviour, but firstly, it is better to classify grease lubrication phases to comprehend the possible role of NPs. It is possible to classify the grease lubricating phases into two stages, based on the film thickness.…”
Section: Nps Tribological Role In Greases Form Evs Lubrication Perspe...mentioning
confidence: 99%
“…Only a few studies have been presented in investigating the use of nanocomposites in greases 44,51,57 . For instance, He et al demonstrated that composite grease based on ZnO‐Si 3 N 4 NPs has excellent potential for vibration reduction and temperature rise in high‐speed bearings (55 000 rpm), coupled with excellent properties of lubrication and antifriction 58 …”
Section: Nps Ability To Enhance Grease Performancementioning
confidence: 99%
“…The lubrication regimes can vary from border lubrication, characterized by substantial direct contact with surface irregularities, to mixed and dynamic lubrication, where a lubricant coating is present to minimize wear and friction (Lee et al 2021). Examining the shift between these lubrication regimes offers an essential understanding of the circumstances in which Si 3 N 4 and steel can attain optimal effectiveness and lifespan (He et al 2018). The tribological efficacy of three commercially available EM lubricates was assessed using the wear and friction of Si 3 N 4 sliding over hardened steel.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Che et al 23 studied the effect of nano zirconium dioxide, silicon dioxide and aluminium oxide in friction materials for automotive brakes and concluded the wear resistance self-lubricating role of nanoparticles at the interface. He et al 24 studied the effect of zinc oxide and silicon nitride nanoparticles as a lubricant and investigated their role in reducing noise. The nanosized spherical molybdenum disulphide in the study of Dong et al 25 was ineffective in reducing the frictional noise and vibration in water-lubricated rubber materials.…”
Section: Introductionmentioning
confidence: 99%